From Boardroom to Control Room: How Governance Structure Shapes Internal Control Success Through Risk Management Channels in Public Investment Entities - Su, Wang; ROZAINI, ROZAINI; Gang, Wang Zhen (Journal of Ecohumanism, 2025)
Focusing on a unique type of state-owned enterprise (SOE), the Chinese Urban Investment Company (CIC), this study delves into the complex relationship between board characteristics, risk management and internal control effectiveness. As a key driver of urbanisation and economic development in China, the study of the governance mechanism of urban investment companies is of great significance. Based on agency theory, resource dependence theory and institutional theory, this paper constructs an integrative analytical framework to examine how board characteristics affect internal control effectiveness, while risk management is used as a mediator and institutional environment as a moderating variable. The study employs panel data of 500 municipal investment companies from 2016 to 2020 and empirically analyses them using advanced econometric methods such as system generalised method of moments estimation (System GMM), threshold regression and multilayer linear model. It is found that board size shows an inverted U-shaped relationship with internal control effectiveness, while board independence and diversity show a positive linear effect. Risk management plays a partial mediating role in the process of board characteristics affecting the effectiveness of internal control, and this role is more significant in urban investment firms facing higher risk exposure. The institutional environment was found to significantly moderate the above relationship. The effect of board characteristics on internal control effectiveness is weakened in regions with high government intervention, while it is strengthened in regions with more developed financial markets. Dynamic analyses through vector autoregressive models show that there is a lagged effect of board characteristics on internal control effectiveness, which usually peaks after 1-2 years. This study extends the theory of corporate governance to the specific context of municipal investment firms, reveals the "black box" process by which board characteristics affect internal control effectiveness, and highlights the important role of institutional factors in shaping governance outcomes. The findings provide valuable insights for policy makers and managers of CICs, which can help optimise board structure, enhance risk management practices, improve internal control systems, and ultimately promote the sustainable development of CICs and reduce systemic financial risks in the Chinese economy.